2015
DOI: 10.1016/j.molimm.2015.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity in ELISA with DNA-loaded nucleosomes in patients with proliferative lupus nephritis

Abstract: Autoantibodies against nucleosomes are considered a hallmark of systemic lupus erythematosus (SLE). We compared in patients with proliferative lupus nephritis the diagnostic usefulness of a dsDNA-loaded nucleosome ELISA (anti-dsDNA-NcX) with ELISAs in which dsDNA or nucleosomes alone were coated. First, we analysed whether DNA loading on nucleosomes led to masking of epitopes by using defined monoclonal anti-DNA, anti-histone and nucleosome-specific autoantibodies to evaluate the accessibility of nucleosomal e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Immunomonitoring of the humoral autoimmune response in SLE is challenging because a wide variety of autoantibodies mediate organ damage directly or indirectly through the formation of ICs [ 2 ], which subsequently trigger the complement system and NET formation [ 6 , 9 ]. Anti-dsDNA [ 39 ], -histones [ 40 ], -nucleosomes [ 41 ] and -C1q [ 42 ] autoantibodies were shown to be involved in IC formation, correlated with disease activity, and thereby are closely linked to the pathogenesis of SLE. Specifically, anti-C1q antibodies have a pathogenic role in LN, because they activated the classical and lectin pathway of the complement system [ 43 ], and C1q-containing ICs are found in the glomeruli [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Immunomonitoring of the humoral autoimmune response in SLE is challenging because a wide variety of autoantibodies mediate organ damage directly or indirectly through the formation of ICs [ 2 ], which subsequently trigger the complement system and NET formation [ 6 , 9 ]. Anti-dsDNA [ 39 ], -histones [ 40 ], -nucleosomes [ 41 ] and -C1q [ 42 ] autoantibodies were shown to be involved in IC formation, correlated with disease activity, and thereby are closely linked to the pathogenesis of SLE. Specifically, anti-C1q antibodies have a pathogenic role in LN, because they activated the classical and lectin pathway of the complement system [ 43 ], and C1q-containing ICs are found in the glomeruli [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…In most SLE cases, serum anti-dsDNA and anti-nucleosome antibodies are presented at the same time [39]. Furthermore, chromatin immunization induces not only anti-nucleosome but also anti-dsDNA and anti-nucleosome antibodies, possibly through epitope spreading [40].…”
Section: Antibodies Induced By Immunizationmentioning
confidence: 99%
“…We have identified that release of DNA and activation of TLR9 is an important injury pathway in acetaminophen induced liver injury, pancreatitis and nonalcoholic steatohepatitis [ 21 – 23 ]. Others have shown this pathway to be important in systemic lupus erythematosus (SLE), and liver ischemia reperfusion injury [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%